A psychospiritual theory of general factor p - Kelley, Thomas M. (Journal for the Study of Spirituality, 2025)
Research points to a single factor known as general factor p that can account for people’s liability to psychopathology, comorbidity among psychopathologies and the severity of psychopathology. Here, we speculate that this common psychopathology factor is an insufficient understanding of the way the human psychospiritual system (or HPS) works. We first describe the Principles that we posit account for the operation of the HPS. Then we propose a process from an insufficient understanding of the way the HPS works to psychopathology. Finally, we present a study that tests our theory of factor p with 851 participants with varying levels of understanding of the way the HPS works. The findings support our theory of p. The mediation analyses show that the level of understanding of the way the HPS works significantly mediates the relationship between maladaptive repetitive thought and psychopathology, and between maladaptive repetitive thought and mental health. Also, as predicted in both relationships, the level of understanding of innate mental health is an even stronger mediator than the level of understanding of the Principle of Thought. The application of these findings to psychopathology prevention and treatment is discussed.